Urbanization and fragmentation have opposing effects on soil nitrogen availability in temperate forest ecosystems. Issue 8 (2nd February 2023) - Caron, Stephen; Garvey, Sarah M.; Gewirtzman, Jonathan; Schultz, Kyle; Bhatnagar, Jennifer M.; Driscoll, Charles; Hutyra, Lucy R.; Templer, Pamela H.
Abstract: Nitrogen (N) availability relative to plant demand has been declining in recent years in terrestrial ecosystems throughout the world, a phenomenon known as N oligotrophication. The temperate forests of the northeastern U.S. have experienced a particularly steep decline in bioavailable N, which is expected to be exacerbated by climate change. This region has also experienced rapid urban expansion in recent decades that leads to forest fragmentation, and it is unknown whether and how these changes affect N availability and uptake by forest trees. Many studies have examined the impact of either urbanization or forest fragmentation on nitrogen (N) cycling, but none to our knowledge have focused on the combined effects of these co‐occurring environmental changes. We examined the effects of urbanization and fragmentation on oak‐dominated ( Quercus spp.) forests along an urban to rural gradient from Boston to central Massachusetts (MA). At eight study sites along the urbanization gradient, plant and soil measurements were made along a 90 m transect from a developed edge to an intact forest interior. Rates of net ammonification, net mineralization, and foliar N concentrations were significantly higher in urban than rural sites, while net nitrification and foliar C:N were not different between urban and rural forests. At urban sites, foliar N and net ammonification and mineralization were higher at forest interiors compared to edges, while net nitrification and foliar C:N were higher at rural forest edges than interiors. These results indicate that urban forests in the northeastern U.S. have greater soil N availability and N uptake by trees compared to rural forests, counteracting the trend for widespread N oligotrophication in temperate forests around the globe. Such increases in available N are diminished at forest edges, however, demonstrating that forest fragmentation has the opposite effect of urbanization on coupled N availability and demand by trees. Abstract : Bio‐available nitrogen (N) has been declining in temperate forests throughout the world, but we find that urbanization may relieve this N decline through increased soil N cycling rates and subsequent N uptake by trees. However, conditions at the forest edge, which are often created during urban expansion, negate increases in soil N cycling rates.